2010
DOI: 10.1016/j.mseb.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The bactericidal effect of carbon nanotube/agar composites irradiated with near-infrared light on Streptococcus mutans

Abstract: Dental caries are mainly associated with oral pathogens, and Streptococcus 2 mutans is a primary cariogenic organism. Many methods have been established to eliminate S. mutans from the oral cavity. This study aimed to evaluate the effect of carbon nanotube (CNT)/agar composites irradiated with near-infrared (NIR) light on S. mutans, as a potential photothermal antimicrobial nanotherapy. A colony-forming unit assay clearly showed that CNT/agar composites attain bactericidal activity after NIR light irradiation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The results demonstrate a definite toxic effect of CNTs in all these studies [10][11][12]. It has been suggested that the cytotoxic effect of CNTs on bacterial cells could have medicinal value by virtue of being bactericidal [13][14][15][16].…”
Section: Introductionmentioning
confidence: 54%
“…The results demonstrate a definite toxic effect of CNTs in all these studies [10][11][12]. It has been suggested that the cytotoxic effect of CNTs on bacterial cells could have medicinal value by virtue of being bactericidal [13][14][15][16].…”
Section: Introductionmentioning
confidence: 54%
“…Alginate and carbon nanotube based composite for the fabrication of biomaterial scaffold [69,70], antibodies based immunosensor [71], and adsorbent for wastewater treatment [72] was earlier studied by various authors. Composites having therapeutic applications were earlier developed by using carbon nanotubes and two oppositely charged biopolymers (chitosan and carrageenan) [73], agar [74], or agarose [75]. Furthermore, for packaging applications free standing composite films were prepared by using κ-carrageenan and carbon nanotubes [76], or single and multi-walled carbon nanotubes [77].…”
Section: Seaweed Based Nanocomposite Materialsmentioning
confidence: 99%
“…About 5 Â 10 7 cells per ml of bacterial or yeast strains were incubated in PBS at 37 C (P. aeruginosa and S. aureus) or at 28 C (C. albicans) with CNTs at 100 mg ml À1 under shaking for 24 h. We employed the described CNT concentration taking into account that the concentrations used in literature to assay antimicrobial activity of CNTs ranged from 10 to 250 mg ml À1 . [13][14][15] Aliquots of bacteria or yeast samples were withdrawn, diluted and then spread onto LB or YPD agar plates, respectively. Aer incubation at the appropriate temperatures, the CFUs were counted.…”
Section: Cell Viability Testmentioning
confidence: 99%